Analysis of Hepatitis A Outbreak in High School X Lamongan District 2018 - Fitrah Bintan Harisma; Fariani Syahrul; Teguh Mubawadi; Yudied Agung Mirasa (Universitas Airlangga, 2018)
Background: Hepatitis A outbreaks were reported by the Lamongan District Health Office to the Surabaya Center for Environmental Health and Disease Control Engineering on January 16, 2018, indicated by an increase in hepatitis A cases in of G and S areas, B village. One of initial sufferer was students in High School X.. Purpose: This study aims to identify the epidemiological characteristics of hepatitis A outbreaks that occur in High School X and the risk factors. Methods: The investigation was carried out in an observational manner with a cross sectional approach. Data were collected by structured interviews, hepatitis A antibodies in blood samples assay, environmental observation, and water samples assay. Data were collected with purposive determination of respondents. Results: Hepatitis A outbreaks at High School X in Lamongan District take place from November 2017 to january 2018, with a target group of 33 students. The epidemic cased tends to be extend common source. Risk factors are contact history with patients, eating habits together in same place, mutual exchange and sharing same eating utensils, the lack of hygiene habit (such as washing hands with soap for students and food handlers), lack of hand washing facilities, bad sanitation, bad food hygiene management, and inadequate clean and hygienis water source. Conclusion: The outbreaks of hepatitis A was extended with the most important risk factors, i.e. lack of personal hygiene and sanitation of water sources.